Effects of a responsible retailing mystery shop intervention on age verification by servers and clerks in alcohol outlets: A cluster randomised cross‐over trial. (9th July 2018) - Grube, Joel W.; DeJong, William; DeJong, Maureen; Lipperman‐Kreda, Sharon; Krevor, Brad S.
Abstract: Introduction and Aims: Clerks and servers at alcohol establishments often fail to verify age. Using mystery shoppers to provide performance feedback is one approach to improving age verification. Few controlled studies have evaluated mystery shop interventions. This paper reports on a cluster randomised cross‐over trial of a mystery shop intervention in 16 communities in four US states. Design and Methods: The intervention comprised monthly mystery shops after which clerks and servers received immediate feedback to reinforce age verification. Managers received monthly reports. Communities in each state were matched into pairs and, following a 3‐month baseline, were randomly assigned within each pair to receive the intervention beginning after the fourth (Early Intervention) or the tenth (Delayed Intervention) mystery shop. On average, 17 (range = 14–20) randomly selected on‐premises and 18 (range = 11–23) off‐premises outlets participated in each community ( N = 557). Results: Fixed effects multi‐level logistic regressions indicated that the intervention led to a two‐fold increase in the odds of age verification, odds ratio (OR) = 2.05; P < 0.001; 95% confidence interval (CI) 1.76, 2.39. Overall, ID‐checking increased from an average of 80% pre‐intervention to 94–96% by the end of the program. Significant effects were found for on‐premises, OR = 1.79; P < 0.001; 95% CI 1.43, 2.24, and off‐premises establishments, OR = 2.29; P < 0.001; 95% CI 1.86, 2.82. Discussion and Conclusions: Mystery shop interventions can increase age verification for alcohol purchases and may be an effective supplement to compliance checks and responsible beverage service programs.